High Prevalence of Vitamin D Deficiency in Cambodian Women: A Common Deficiency in a Sunny Country - Smith, Geoffry (Nutrients, 2016)
Recent studies have shown that in spite of being generally close to the equator; vitamin D deficiency is common in South East Asian countries. In order to quantify micronutrient status for women and children in Cambodia; a nationally-representative survey was conducted in 2014 linked to the Cambodian Demographic Health Survey. The countrywide median of 25(OH)D was, respectively, 64.9 and 91.1 nmol/L for mothers and children. Based on The Endocrine Society cutoffs (>50<75 nmol/L = insufficiency; ≤50 nmol/L = deficiency); 64.6% of mothers and 34.8% of their children had plasma vitamin D concentrations indicating insufficiency or deficiency. For deficiency alone, 29% of the mothers were found to be vitamin D deficient, but only 13.4% of children. Children who live in urban areas had a 43% higher rate of vitamin D insufficiency versus those who live in rural areas (OR; 1.434; 95% CI: 1.007; 2.041). However, such differences were not observed in their mothers. The high prevalence of vitamin D deficiency is likely in part due to lifestyle choices, including sun avoidance, increasingly predominant indoor work, and covered transport. These survey findings support the need for a broader national Cambodian study incorporating testing of adult men, adolescents and the elderly, and encompassing other parameters such as skeletal health. However, the data presented in this study already show significant deficiencies which need to be addressed and we discuss the benefit of establishing nationally-mandated food fortification programs to enhance the intake of vitamin D.